Factors affecting the anthelmintic efficacy of papaya latex in vivo: host sex and intensity of infection - Luoga W.; Mansur F.; Lowe A.; Duce I.R.; Buttle D.J.; Behnke J.M. (Springer Verlag, 2024)
Indexed by WOS/ Scopus